Implementation of an educational programme for caregivers of the elderly in Windhoek and Rehoboth, Namibia - Kloppers, Joan.M; van Dyk, Agnes; N. Nelumbu, Lucia (International Journal of Medicine, 2015)
In many instances care for the frail elderly, especially in long-term care institutions, is provided under minimal supervision by caregivers who lay people. This can lead to poor-quality care or neglect of the frail elderly. Therefore, caregivers have a major role in coordinating comprehensive long-term care.One of the objectives of the study â€œCaregiving in old-age homes in Windhoek: A practice-orientated enquiry into caregiving educationâ€ was to implement the educational programme for caregivers in old age homes in Windhoek. A qualitative, explorative, descriptive, contextual and phenomenology design was used to perform this study.The study was conducted in three phases. Firstly, a situational analysis was carried out to explore and describe the experiences and needs of the caregivers and the elderly. The situation analysis revealed themes in terms of interpersonal relationships that could be positive or negative regarding the elderly, with the sub-themes like communication, support and caring for elderly people. These themes and sub-themes include the following: Interpersonal relationships were viewed as an important aspect of the caring process. Lack of regular in-service training sessions for caregivers, with a sub- theme of a lack of adequate knowledge of procedures. Lack of human resources, equipment and policiesIn the second phase, a conceptual framework was derived from the results of phase 1, using the activities prescribed by Dickoff, James and Wiedenbach (1968). In the third phase, a programme was developed from the findings of the previous phase. Finally, the educational programme was implemented and evaluated in old-age homes in Windhoek.